2021
DOI: 10.1186/s12935-021-01989-7
|View full text |Cite
|
Sign up to set email alerts
|

YWHAE as an HE4 interacting protein can influence the malignant behaviour of ovarian cancer by regulating the PI3K/AKT and MAPK pathways

Abstract: Background Malignant tumours of the female reproductive system threaten the lives and health of women worldwide, with ovarian cancer having the highest mortality rate. Based on previous work, this study analysed the expression and role of YWHAE in ovarian epithelial tumours. Methods The interaction between YWHAE and HE4 was evaluated via immunoprecipitation, western blot analysis, and cellular immunofluorescence. Immunohistochemistry was used to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Likewise, MACC1 induced β-catenin expression and phosphorylation, an important signaling and adaptor protein in cell–cell junctions ( 169 , 180 , 203 , 215 217 ), negatively regulating E-cadherin ( 208 ). As mentioned earlier, MACC1 interacts with YWHAE which was shown to induce lower E-cadherin but higher N-cadherin and vimentin expression ( 186 ), being another explanation for the observed effects. Arguments for MACC1 acting on cell–cell adhesions and cytoskeletal organization are supported by a study in HeLa cells showing lowered actin staining upon MACC1 silencing ( 218 ) and by experiments on glioblastoma cells showing lower equilibrium cell–cell adhesion after MACC1 overexpression ( 13 ).…”
Section: Macc1 In Tumor Migrationmentioning
confidence: 65%
See 1 more Smart Citation
“…Likewise, MACC1 induced β-catenin expression and phosphorylation, an important signaling and adaptor protein in cell–cell junctions ( 169 , 180 , 203 , 215 217 ), negatively regulating E-cadherin ( 208 ). As mentioned earlier, MACC1 interacts with YWHAE which was shown to induce lower E-cadherin but higher N-cadherin and vimentin expression ( 186 ), being another explanation for the observed effects. Arguments for MACC1 acting on cell–cell adhesions and cytoskeletal organization are supported by a study in HeLa cells showing lowered actin staining upon MACC1 silencing ( 218 ) and by experiments on glioblastoma cells showing lower equilibrium cell–cell adhesion after MACC1 overexpression ( 13 ).…”
Section: Macc1 In Tumor Migrationmentioning
confidence: 65%
“…Yet, MACC1 may affect PI3K/AKT signaling also via direct interactions with YWHAE (14-3-3 epsilon), as confirmed by affinity capture-MS ( 185 ). YWHAE was previously found to induce PI3K and AKT activation ( 186 ). Additionally, PTEN was reported to suppress cell–matrix adhesion-associated tumor cell migration by inhibition of FAK ( 187 ) and further induce N-cadherin and suppress E-cadherin ( 188 ), while PI3K/Akt signaling had the opposite effects ( 189 ).…”
Section: Macc1 In Tumor Migrationmentioning
confidence: 99%
“…YWHAE can acts as an HE4-interacting protein that can influence the malignant behavior of OV by regulating the phosphatidylinositol 3-kinase (PI3K)/AKT and mitogen-activated protein kinase pathways. 34 YWHAE enhances invasion, migration, and proliferation, and inhibits apoptosis in OV cells. 34 Despite the correlation between YWHAE and YWHAEP1 genes, further studies are needed to elucidate their specific relationships and interactions.…”
Section: Resultsmentioning
confidence: 99%
“… 34 YWHAE enhances invasion, migration, and proliferation, and inhibits apoptosis in OV cells. 34 Despite the correlation between YWHAE and YWHAEP1 genes, further studies are needed to elucidate their specific relationships and interactions.
Figure 7 cis -edQTLs in OV subtypes (A) Manhattan plot of the FDR for each A-to-I editing site in cis -edQTL mapping.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the PI3K/AKT and MAPK signaling pathways are essential for EOC progression ( 22 , 23 ). We retrieved the downregulated gene sets from the PI3K/AKT and MAPK signaling pathways, and the results of the two gene sets were integrated by drawing a Venn diagram.…”
Section: Resultsmentioning
confidence: 99%